If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+7-3x=39
We move all terms to the left:
9x+7-3x-(39)=0
We add all the numbers together, and all the variables
6x-32=0
We move all terms containing x to the left, all other terms to the right
6x=32
x=32/6
x=5+1/3
| y2=100 | | 3x+10= 2x+3 | | -7w+4(w-2)=-20 | | (3x9)+2/3=55 | | 3x9+2/3=55 | | 3x-3+130=14x+6 | | 24-3h=7h+4 | | x=9+0.53/0.83 | | 0.83x=8 | | 7=-14x=35 | | 6x-5x=35 | | 0.8x=33 | | 3x-2=2x+13/3 | | 4x+50=4x+18 | | 12x-4x+124=12x+64 | | -3(-+4)=-(4x+14) | | 8(2-5)+5z=2-12 | | X+9+3x-6=-17 | | 4y-8=1 | | 9=5(u+3)-2u | | 3(5x+9)=-48+45 | | 8(c+9)-1=5(c+4) | | 32-7x=17+8x | | 3x+26=55 | | 9/2b+11-5/6b=b+2 | | 32-7x=17=8x | | 14q-2(5q-17)=-3(-5q-15) | | 2(x-7)+8x=6 | | -11x-30+6x=0 | | -6h=5(-h-13) | | 4^5x-7=7^2x-9 | | p×p+5÷3p=-7 |